HÁR QÍYLÍ ANTIDETONACIYALÍQ QOSÍMSHALARDÍŃ BENZIN HÁM ONÍŃ KOMPONENTLERІNIŃ SHÓKPE PAYDA ETIW QASIYETINE TÁSIRІ - Ametova, D.M.; Artıkbaeva, B.R. (SCIENCE and SOCIETY, 2022)
Studied osmolality mixtures of gasolines of different nature with different content of actual pitches. It is proved that osmolality mixtures of gasoline is non-additive in nature. The introduction of oxygenates in the composition of gasoline of different nature leads to a decrease in their osmolality. Low-molecular alcohols and amines, as well as esters of the MTBE type, have a greater positive synergistic effect.